Recurrent pleural effusion as a rare manifestation after prolonged PD1 inhibitor (camrelizumab)-based immunotherapy: A case report - Xiao-Hong Xie; Pan-Xiao Shen; Jian-Hui Wu; Gui-Huan Qiu; Xin-Qing Lin; Zhan-Hong Xie; Yin-Yin Qin; Bin Zheng; Ming Liu; Cheng-Zhi Zhou (Taylor & Francis Group, 2023)
Immune-related adverse events (irAEs) pose a significant challenge for the widespread adoption of immuno-oncology therapies, but their symptoms can vary widely. In particular, the relationship between irAEs and pleural effusion (PE) in patients with advanced non-small cell lung cancer (NSCLC) remains unclear. In this report, we present the case of an advanced NSCLC patient who developed persistent PE despite receiving camrelizumab (an anti-programmed death receptor 1 [PD-1] antibody) and chemotherapy as first-line treatment. While the patient's tumor biomarkers decreased after multiple cycles of treatment, the PE persisted despite negative findings on cytology and pleural biopsy. Additionally, the use of anti-angiogenic drugs failed to alleviate the PE. Screening for rheumatic connective tissue markers and tuberculosis yielded negative results, but intrathoracic dexamethasone injections in two doses resulted in a significant reduction of the PE. This case suggests that PE may represent a rare type of irAE that should be monitored for during prolonged immuno-oncology therapy.